IMMUNOHISTOCHEMICAL ANALYSIS AS A METHOD FOR INCREASING THE DETECTION OF PROSTATE CANCER IN PRIMARY BIOPSY - S. V. Popov; R. G. Guseynov; O. N. Skryabin; I. N. Orlov; A. A. Vorobyov; A. G. Martov; V. L. Shchukin (Исследования и практика в медицине)
Morphological manifestations of prostate cancer (PCa) in 15–20% of cases are similar to those with benign hyperplastic processes in prostate tissue and/or with a histological pattern of atypical small acinar proliferation (ASAP).The purpose of this study is a comparative study of the detection of prostate cancer in biopsy material using a review morphological analysis and immunohistochemistry with the use of monoclonal antibodies to the nuclear p63 protein, high molecular weight cytokeratins of clone 34βE12 and α-methylacyl-CoA-racemase.Materials and methods. The method of the study was a retrospective analysis of the findings on the review morphological and immunohistochemical (IHC) analyzes of biopsy material of 428 patients who were examined and treated in the urological hospital for the period from 2013 to 2017.Results. Almost half of the cases of ASAP, determined by routine histological examination of biopsy specimens with hematoxylin-eosin staining, in the process of IHC analysis using monoclonal antibodies to the nuclear protein p63, cytokeratins of clone 34βE12 and α-methylacyl-CoA racemase were verified for prostate cancer. The number of histological findings on benign prostatic hyperplasia detected in routinely stained preparations decreased by 12.38% in favor of the histological diagnosis of prostate cancer after the IHC study.Conclusion. Immunohistochemical analysis of biopsy material using monoclonal antibodies to nuclear p63, high-molecular cytokeratins of clone 34βE12 and α-methylacyl-CoA racemase for suspected prostate cancer: firstly, specifies the micromorphological picture and demasks prostate cancer; secondly, it increases the detectability of prostate cancer; thirdly, it reduces the occurrence of false-negative results.